Psychological distress among cancer patients on chemotherapy - Zainal, Nor Zuraida; Ng, Chong Guan (University of Malaya Medical Centre, 2010)
Distress has become a major issue in cancer population. Patients may suffer from either physical, psychological distress or both. Cancer patients who are undergoing chemotherapy are more likely to experience psychological distress. This could be due to the negative effects of chemotherapy agents, the uncertainty of post-treatment, and the occurrence of psychosocial problems. As a result, the patient may experience a normal reaction such as sadness or may develop common psychiatric disorders such as depression and anxiety.